Cinic foucault: the historical ontology of ourselves and the necessary possibility of another life - Inchauspe, Emilio (2020)
The present work makes use of Foucaultian’s reading of ancient cynicism to propose a possible interpretation of Foucault’s work, and in particular, of the complex link between truth, power and the subject. Thus, we will say that the affirmation “true life is another life”, fits both Foucault’s cynics and the professor himself. In fact, his project of a historical ontology of ourselves leads to an “eventualization” of the present according to which it is always possible for it to be transformed, with which we can say that Foucault also maintains that “another life” is true. In order to justify this, we will first mention the central character of the dimensions of truth, power and the subject in Foucault’s historical ontology of ourselves, and then show how power relations, in their productive character, are the common denominator in the way these dimensions are articulated. In this way we will see how this “eventualization” of the present supposes that true life can always be another.